Brute force algorithm implementation for traveljoy travelling recommendation system - K.A.F.A. Samah; N. Sabri; R. Hamzah; R. Roslan; N.A. Mangshor; A.A.M. Asri (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents the Brute Force algorithm implementation for TravelJoy Travelling Recommendation System.  Due to overwhelmed information in the internet, travelers faced difficulties in finding and comparing which places in Melaka that worth to visit. Melaka is a well-known place as one of the most popular tourist spots in Malaysia, famous with historical places. All the mentioned problems were time-consuming and required lots of efforts for manual comparison between places and planning the trip itinerary. An efficient application system is needed to assist travelers in planning their trip itinerary by providing details of interesting place in Melaka, budget estimating and recommendation of sequence places which to visit. The TravelJoy application applied Traveling Salesman Problem (TSP) concept using Brute Force algorithm in determining the least time duration for the selected places and adapting Expected Time Arrival (ETA). It was found through Brute Force algorithm adaptation; the recommendation system is reliable based on the functional and reliability testing with t-test result of 0.00067, indicates the system is accepted.